Analisis Penerapan Standar Pelayanan Minimal (SPM) Orang dengan Risiko Terinfeksi Virus HIV di Puskesmas Bukit Sangkal Kota Palembang Tahun 2024 - Putri Aqmah Cahyani; Najmah Najmah; Khaila Sugma Khairunisa; Theresia Utpala Febriyanti; Andi Gilang Perdana; Muhammad Fahrizal; Sasha Tiara Maharani; Harmadi Harmadi; Rica Syafrida Putri; Dinia Ismarini (JURNAL BIDANG ILMU KESEHATAN, 2025)
The increasing incidence of Human Immunodeficiency Virus (HIV) in Indonesia, especially among the productive age group, emphasizes the urgency of quality healthcare implementation. The government has set Minimum Service Standards (SPM) as mandatory guidelines for regions, including services for high-risk HIV groups. This study aimed to analyze the achievement level of HIV-related SPM and the quality of resources at Bukit Sangkal Health Center, Palembang, in 2024. A descriptive quantitative approach was used, based on secondary data from the health center’s HIV program report. The findings revealed varied levels of HIV service coverage: pregnant women (126.6%), TB patients (46.9%), STIs (54.2%), MSM (4.4%), and no coverage for transgender individuals and female sex workers. The availability of supporting facilities reached 96.6%, while human resources were only at 80% due to the absence of nursing staff. The overall service quality index stood at 88.3%. The study concludes that although some groups exceeded targets, substantial disparities persist among key populations. Community-based outreach strategies and strengthened intersectoral collaboration are needed to address these gaps and improve the overall quality of HIV services.